Multiscale fabrication of functional materials for regenerative medicine - Bianchi, Michele; SpringerLink (Online service). (Berlin New York Springer, 2011)
Regenerative medicine demands new concepts and fabrication tools to improve our common knowledge about cell-cell and cell-environment interactions. In this work, Michele Bianchi  shows that different kinds of signals, such as chemical, topographical, and electrical signals,  can be arranged in a highly-controlled way. Furthermore, Michele uses scale lengths ranging from several micrometers to a few nanometers, through the employment of unconventional fabrication techniques. For each signal, Michele chose properly designed materials and fabrication methods. The external signals are capable of controlling cell adhesion and growth, opening the way for a systematic investigation of the environmental features affecting cell behavior.
Introduction -- Experimental Techniques -- Stable Non-Covalent Functionalization Of Teflon-AF (Chemical Control) -- Multiscale Patterning Of TiO2 For Cell Growth Control (Topographical Control) -- Control Of Neural Cell Adhesion On 3D-SWCNT (Electrical Control) -- Lithographical Controlled Etching (Appendix).
Electronic reproduction.
Keywords: Nanomedicine; Biomedical materials; Regenerative medicine; Electronic books